2009
DOI: 10.1097/brs.0b013e3181a9d28e
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Open Versus Conventional Open Posterior Lumbar Interbody Fusion for the Treatment of Lumbar Degenerative Spondylolisthesis

Abstract: Mini-open PLIF is safe and effective. Mini-open PLIF was less invasive than open PLIF with regard to the MF muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
93
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 32 publications
(18 reference statements)
7
93
3
Order By: Relevance
“…Two studies in our systematic review did demonstrate improved early outcome scores in MIS PLIF over open PLIF; however, this effect was noticed during the early timeframe postoperatively and became negligible at [ 1-year followup. However, five studies did not find a benefit to MIS PLIF over open PLIF in terms of validated outcomes scores [4,11,20,26,28]. This suggests MIS may result in a quicker decrease in postoperative pain and functional recovery, but no studies in our review evaluated return to work status for patients.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Two studies in our systematic review did demonstrate improved early outcome scores in MIS PLIF over open PLIF; however, this effect was noticed during the early timeframe postoperatively and became negligible at [ 1-year followup. However, five studies did not find a benefit to MIS PLIF over open PLIF in terms of validated outcomes scores [4,11,20,26,28]. This suggests MIS may result in a quicker decrease in postoperative pain and functional recovery, but no studies in our review evaluated return to work status for patients.…”
Section: Discussionmentioning
confidence: 77%
“…Compared with posterolateral and lateral approaches, PLIF may be advantageous, providing a wider area of intervertebral interbody graft bone contact surface, improved load-sharing, adequate access for complete decompression of the neural elements, restoration of neural foraminal height, and the ability to restore segmental lordosis at the involved level [1-3, 5, 10]. Multiple studies report a high fusion rate ranging between 89% and 97% with this technique [4,7,11,18,26,30,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of minimally invasive spine surgery (MIS) is that it reduces paraspinal muscular injury. Previous studies comparing MIS and conventional surgical techniques showed that MIS caused less damage to the paraspinal muscle, as determined by assessing the degree of atrophy and T2-signal intensity [6,10,[12][13][14]. However, some controversy remains as to whether the advantages of MIS are reflected by improved clinical outcomes, as assessed using measures such as VAS scores for low back pain, the Oswestry disability index, or the JOA score [6,10,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unilateral laminotomy for bilateral decompression of lumbar spinal stenosis is expected to preserve the paraspinal muscles on the contralateral side of the approach [8]. The Wiltse et al [9] approach for insertion of pedicle screws (PSs) is also considered a less invasive technique that helps preserve paraspinal musculature [10]. A major advantage of all these techniques is the reduction in iatrogenic paraspinal muscular injury, because damage to these muscles, can lead to denervation and atrophy and thus increased the risk of ''fusion disease'' [1,11].…”
Section: Introductionmentioning
confidence: 99%